1999
DOI: 10.1159/000016641
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Study of Cryopreserved Human Corneal Endothelium

Abstract: The aim of the present paper is to describe the morphological changes that occur in human corneal endothelium as an immediate consequence of corneal cryopreservation. Therefore, 16 human donor corneas were cryopreserved with an original procedure at a 1 °C/min cooling rate in a freezing solution cryoprotected with 7% dimethylsulphoxide until a final temperature of –100 °C was reached. After storage of the corneas in liquid nitrogen for periods ranging from 1 to 96 days (mean: 34.31 days), the corneas were thaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Our results confirm data published by other authors who have described the structural disruption of corneal endothelial cells and other changes after cryopreservation (Wusteman 1997;Canals 1999). In addition to this, we have used TEM to quantify the relative contribution of apoptosis versus necrosis in keratocyte cell death.…”
Section: Discussionsupporting
confidence: 89%
“…Our results confirm data published by other authors who have described the structural disruption of corneal endothelial cells and other changes after cryopreservation (Wusteman 1997;Canals 1999). In addition to this, we have used TEM to quantify the relative contribution of apoptosis versus necrosis in keratocyte cell death.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the disruption of the intercellular adhesion of endothelial layers limits the lifespan of cold-stored organs for transplant [Carles et al, 1994;Eberl et al, 1999]. In particular, the lifespan of cold-stored eye bank corneas is limited by the gradual loss of endothelial integrity [Armitage, 2008;Day et al, 2008], in part due to alterations of the actin cytoskeleton and of the intercellular junctions [Canals et al, 1999;Hsu et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been reported on cryoprotection of porcine cornea in dextran and Me 2 SO of concentrations higher than those used in our experimental system (Canals et al, 1996;Wusterman et al, 1999). The human cornea has been shown to successfully recover from freezing cryoprotected in Me 2 SO (Canals et al, 1999), Me 2 SO, formamide and 1,2-propanediol , Me 2 SO, glycerol and 2,3-butanediol . Although the results of these experiments have been satisfactory, the damage cannot be completely avoided using these cryoprotectors.…”
Section: Discussionmentioning
confidence: 86%